Pāratitācaṉ kavitaip peruveḷi - Ciṟpi (Kavitā Papḷikēṣaṉ, 2020)
Critical study on the works of Bharathidasan, 1891-1964, eminent Tamil poet; includes selected poems; previously serialized in Om Sakthi, Tamil monthly during 2017-18.
Keywords: Pāratitācan̲; 1891-1964; Criticism and interpretation.; Tamil poetry.